Whispers at Painswick Court - Klassen, Julie, 1964- (Bethany House Publishers, a division of Baker Publishing Group, 2025)
"Surgeon's daughter Anne Loveday serves as sickroom nurse to a lady at a Cotswolds manor. While navigating the other residents--including potential suitors--a series of mishaps befalls her patient, and Anne realizes there may be a murderer in their midst. With her reputation and heart on the line, can she discover who's guilty before it's too late?"-- Provided by publisher.